El despertar de una gran ciudad: Madrid - CARBALLO BARRAL, Borja (Cuadernos de Historia Contemporánea, 2010)
The origin of the social, economic, political and cultural transformations that turned Madrid into a metropolis during the first third of the 20th century, is the result of combining three elements: surplus water, railroad and urban enlargement. This article shows the main results obtained in relation to the Madrilenian urban growth during the second half of the 19thth century through the study of Madrid´s municipal registers. Focusing on the Eastern margins of its extension, it analyses the migratory process that formed its demographic reality, the consolidation of its inhabitants’ urban segregation and the germination of a labor market divided according to gender, and where the location in the city was a variable to consider.